2000
DOI: 10.1016/s0278-6915(00)00032-6
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics and metabolism of sucralose in the mouse

Abstract: The excretion and metabolism of (14)C-sucralose has been investigated in mice following intravenous and oral administration. A 20mg/kg intravenous dose was rapidly excreted mainly in the urine (80% in 5 days). After 100, 1500 and 3000mg/kg oral doses of (14)C-sucralose, means of 23%, 15% and 16% of the dose, respectively, were excreted in the urine during 5 days. Comparison with the intravenous dose indicated that 20-30% of the oral doses was absorbed. Sucralose was excreted almost entirely unchanged and repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 2 publications
3
24
1
Order By: Relevance
“…In the case of NAS, one may consider a direct effect, in which bacteria that can metabolize NAS as energy source thrive, while others may experience toxicity. Such a direct effect is indeed plausible in the case of saccharin and sucralose, as both are largely not metabolized by the host's body 35,57 and have been previously demonstrated to affect the growth of certain bacteria. [58][59][60] Our findings suggest such direct effect of saccharin on the microbiome, and functional analysis of the saccharin-associated metagenome indicated that several pathways involved in metabolism of heterocyclic compounds were enriched, suggesting that saccharin exposure may have been associated with expansion of bacteria capable of utilizing it.…”
Section: Challenges: Toward Mechanistic Understanding Of Nas Effectsmentioning
confidence: 92%
See 1 more Smart Citation
“…In the case of NAS, one may consider a direct effect, in which bacteria that can metabolize NAS as energy source thrive, while others may experience toxicity. Such a direct effect is indeed plausible in the case of saccharin and sucralose, as both are largely not metabolized by the host's body 35,57 and have been previously demonstrated to affect the growth of certain bacteria. [58][59][60] Our findings suggest such direct effect of saccharin on the microbiome, and functional analysis of the saccharin-associated metagenome indicated that several pathways involved in metabolism of heterocyclic compounds were enriched, suggesting that saccharin exposure may have been associated with expansion of bacteria capable of utilizing it.…”
Section: Challenges: Toward Mechanistic Understanding Of Nas Effectsmentioning
confidence: 92%
“…Most NAS are excreted unchanged from the mammalian body, and therefore considered metabolically 'inert' [33][34][35] with no physiological effect exerted on the mammalian host. While these 2 notions form the foundation for the endorsement of NAS use, lack of NAS metabolism by the host does not rule out the possibility that these compounds may interact with the gut microbiome.…”
Section: Nas and The Microbiomementioning
confidence: 99%
“…Studies performed on the metabolism of sucralose showed that when administered orally to mice at doses of 1000, 1500 and 3000 mg/kg body weight/day, urinary elimination averaged, respectively 23%, 15% and 16%, indicating that even with augmented administration of sucralose, there is no corresponding rise in absorption [12,13]. Studies indicate the existence of 2 hydrolysis products of sucralose, 4-chloro-4-deoxy-Dgalactose (4-CG) and 1,6-dichloro-1-6-dideoxy-D-fructose (1,6-DCG) that are more rapidly absorbed after oral administration than the original sucralose compound.…”
Section: Introductionmentioning
confidence: 99%
“…Students should also take into consideration evidence from the study discussed in Questions 4 and 5 where an average of 92.8% of radioactivity from 14 C-sucralose was recovered within 5 days indicating the only metabolism of sucralose in humans involves glucuronidation [4]. These results have been supported by studies in dogs, mice, and rats [15][16][17]. 7) Sucralose is a halogenated compound.…”
mentioning
confidence: 91%